Assessment of Place of Delivery and Associated Factors among Pastoralists in Ethiopia: A Systematic Review and Meta-Analysis Evaluation - Lebeza Alemu Tenaw; Henok Kumsa; Mulugeta Wodaje Arage; Atitegeb Abera; Tilahun Hailu; Esuyawkal Mislu (Journal of Pregnancy)
Background. Pastoralist communities rely on their livestock for at least 50% of their food supply and source of income. Home births raise the risk of maternal morbidity and death, whereas institutional births lessen the likelihood of difficulties during labor. Around 70% of labors in pastoralist regions of Ethiopia were assisted by traditional birth attendants. Methods. Studies done from January 2004 to January 2023, accessed in PubMed, EMBASE, Medline, and other search engines, were included. PRISMA guidelines and JBI critical appraisal checklist were used to assure the quality of the review. Ten articles were included in this review. Data were extracted with Excel and exported to STATA 16 for analysis. Heterogeneity of literatures was evaluated using I2 statistics and publication bias using the Egger regression asymmetry test and the Duval and Tweedie trim-fill analysis. Statistical significance was declared at p value less than 0.05. Result. The pooled estimate of institutional delivery among the pastoralist community in Ethiopia is 21.2% (95% CI: 16.2-26.1). Husbands who were involved to decide place of delivery (OR=3.47; 95% CI: 1.61, 7.50), women with good knowledge of MCH services (OR=2.283; 95% CI: 1.51, 3.44), women who had a positive attitude towards MCH services (OR=1.69; 95% CI: 0.79, 3.6), availability of health institutions (OR=2.6; 95% CI: 0.95, 7.20), and women who had an ANC follow-up (OR=2.78; 95% CI: 2.07, 3.73) were higher institutional delivery prevalence among pastoralist women. Moreover, institutional delivery among women who were educated above the college level was more than two times (OR=2.56; 95% CI: 1.985, 3.304) higher than among women who were not educated. Conclusion. Pastoralist women in Ethiopia were found to be a disadvantaged group for institutional delivery at national level. Husband involvement, educational level, ANC visit, knowledge and attitude for MCH service, and health facility distance were identified to have significant association with institutional delivery.